Development of Highly Sensitive Ethane Gas Sensor Based on 3D WO3 Nanocone Structure Integrated with Low-Powered In-Plane Microheater and Temperature Sensor - Adib, Md Ridwan; Kondalkar, Vijay V.; Lee, Keekeun (Advanced Materials Technologies, 2020)
Metal oxide nanostructures are the most promising materials for the fabrication of advanced gas sensors over two decades. Especially, reliable responsivity and selectivity for various harmful gases are the main requirements for the future chemiresistive-type gas sensors. Here, a 3D nanocone (NC) of WO3 for a real-time ethane (C2H6) gas sensor is reported. A compact WO3 nanoparticles thin film deposited on the sensor interdigitate electrodes (IDEs) by using radio frequency (RF) sputter and subsequently, WO3 thin film is converted into highly ordered 3D NC with simple monolayer of polystyrene. An in-plane microheater integrated with a temperature sensor is also developed here in which the heater, temperature sensor, and the gas sensor share the same plane instead of a conventional vertical structure where the microheater and the sensor IDE are placed one above the other. Prior to the fabrication, COMSOL simulations are carried away to predict the heater performance and surface charge densities of the NC structures. A comparative study between the planar WO3 and highly ordered 3D NC WO3 in sensor response has been conducted. The fabricated sensors (planar WO3) and 3D NC WO3 show a high response ΔR/R (%) of 44% and 52% to 100 ppm of ethane at 200 °C respectively.
Keywords: Comparative studies; Ethane gas; Fabricated sensors; Micro-heaters; Nano-cones; Nanocone structures; Tungsten oxide; Vertical structures; ethane gas sensors; in-plane microheaters; nanocones; temperature sensors; tungsten oxide